Gentrificação e ordenamento territorial da Avenida Fernando Guilhon: uma análise a partir do instituto da desapropriação - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The discussion about the process of gentrification, territorial planning and expropriation can be the first step towards creating a collective consciousness that proposes the development of spaces and services that connect people, instead of separating them and that preserve the characteristics of a area, a neighborhood and its inhabitants, as the right to property, despite being individual, is conditioned to the well-being of the community due to the obligation to observe the social function, which is enshrined in the Federal Constitution as a fundamental right. In this scenario, there are structural transformations occurring in property rights in the area that covers Avenida Fernando Guilhon, specifically in its ideological basis, with the individualist conception being replaced by a social one to the extent that, in addition to the satisfaction of individual interests, The collective interest of those subjects who are not owners also began to be targeted. The object of study of this research is the process of gentrification and territorial planning of Avenida Fernando Guilhon, in the municipality of Santarém, state of Pará, based on the institute of expropriation, as it presents itself as the result of the fundamental right, which is property , in the sense of, in view of the social function, seeking a new model of urban restructuring through gentrification, a significant mutation which inserted new concepts into the current legal system, substantially modifying it.
Keywords: Desapropriação; Gentrificação; Políticas públicas; Território; CNPQ:: CIÊNCIAS HUMANAS; Políticas públicas e estratégias de desenvolvimento regional, para obtenção do título de mestre.